Wczesnoszkolna edukacja matematyczna. Perspektywa holistyczna - Alina Kalinowska-Iżykowska (Problemy Wczesnej Edukacji)
Holistic education is a concept whose assumptions speak of the whole educational interactions of an exogenous and endogenous nature. The text postulates the thesis that it is possible to view the various areas of knowledge, including mathematics, holistically. Two views show arguments that confirm this possibility. The need to adapt mathematical education to students’ cognitive levels, work in small groups or openness to beauty, as well as fascinating examples of mathematical descriptions of phenomena in nature are basic needs of early classes math education. They also develop competencies relevant to the holistic approach to education, enabling the building of coherent mathematical knowledge in the minds of students and their understanding of the mathematical nature of the world.